The state of the art of research conducted in reading and writing in the experimental school No. 7011-Uladislao Zegarra Araujo of Lima-Peru between the years 50-70, using the Peruvian method as a methodology - Vásquez Paulini, Luis (2016)
The article presents a state of the art of the researches carried out in reading and writing in the Experimental School No. 7011-Uladislao Zegarra Araujo de Lima- Peru between the years 50-70, using as methodology the Peruvian Method. The evaluation of these experiences shows that the trend was oriented to teacher training in innovative methodology and production of educational material, however, solving the problem of illiteracy and helping children with minor retardation or other learning problem was the priority theme and To which he was given the most attention. A questionnaire was developed to address the issue and based on interviews with officials of the Ministry of Education, teachers and students who worked and studied in those years; Focus groups were made with family members of the teachers who were the authors of the method, teachers implemented with the method and students who learned to read and write with this method. The interviews approach allowed to identify and evaluate the advances that were made in the experimental institute within the specific context of reading and writing. The state of the art was supplemented by information from various specialists in the field of reading and writing and the advances of the pedagogical sciences on the subject.